PENGARUH PERCEIVED QUALITY DAN VALUE TERHADAP REPURCHASE INTENTION MELALUI SATISFACTION ROSITA COOKIES - Claudio Jauwena (Jurnal Performa)
This research was conducted to determine whether consumer satisfaction mediates the relationship between perceived quality and perceived value on repurchase intention on Rosita cookies products. Seeing from the interest of consumers in Indonesia towards snacks which continues to increase. In order to collect research data, 140 questionnaires were distributed to respondents aged between 15 to 50 years and had been customers of Rosita cookies with a minimum of 2 transactions. Sampling was carried out using a purposive sampling method. This research was processed using AMOS software. The first result of this study is that perceived quality has a positive and significant effect on consumer satisfaction and repurchase intention. The results of this study are perceived quality and perceived value have a positive and significant effect on repurchase intention by mediating consumer satisfaction. So it can be concluded that these 7 hypotheses are accepted